The Influence of Zikir on the Tabligh Movement in Radda Village, Baebunta Subdistrict, North Luwu Regency - Yusril Emra; Achmad Abubakar; Muhammad Yahya; Amrullah Harun; Zulkifli Yunus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study will examine how dhikr is implemented in daily life by members of the Tabligh Jama'ah, especially in Radda Village, Baebunta District, North Luwu Regency, South Sulawesi. This type of research is field research, namely qualitative research using two approaches, namely the interpretation and sociology approaches. Furthermore, the data sources used are primary data sources through interviews with Tabligh Jama'ah figures and the community in Radda Village. Secondary data is auxiliary data obtained from literature such as journals, books, articles and tafsir books. Data processing and analysis techniques are data editing, data reduction and data presentation. The results of this study indicate that the influence of dhikr on individual members of the Tabligh Jama'ah is seen in inner peace, patience and awareness of closeness to Allah. Dhikr strengthens faith, directs behavior, and has a positive impact on social life, such as fostering brotherhood, caring and improving people's morals.